Influence of Temperature on Structural and Magnetic Properties of Gd3AlxFe5−xO12 (x = 2). Issue 2 (6th December 2021) - Sharma, Anjori; Godara, Sachin Kumar; Maji, Pradip K.; Srivastava, A. K.
Abstract: This research work explores the effect of sintering temperature on morphology and magnetic properties of aluminum substituted gadolinium iron garnet Gd3 Al x Fe5− x O12 ( x = 2). Sol–gel autocombustion method is adopted to prepare Gd3 Al x Fe5− x O12, and further sintered at 900, 1000, and 1100 °C. X‐ray diffraction (XRD) confirms the formation of garnet phase structure. Fourier transformation infrared ray further stands with result of XRD that reveals the presence of garnet phase. Field emission scanning microscope analysis shows the formation of average grain size 4, 6, and 13 nm for 900, 1000, and 1100 °C, respectively. Vibrating sample magnetometer results show that the coercivity decreases with increases in temperature, which indicates that this material can be used in switching devices. The calculated value of microwave operating frequency reveals that these materials can be used in ultrahigh‐frequency region. Abstract : Gd3 Al2 Fe5− x O12 powder is synthesized using the sol–gel autocombustion method. The sample is heated at three different temperatures, i.e., at 900, 1000, and 1100 °C in order to check the influence of these temperatures on the structural and magnetic properties. The sample is characterized using X‐ray diffraction, Fourier transformation infrared ray, field emission scanning microscope, and vibrating sample magnetometer. The main results are presented in the graphical abstract.